KINERJA PEMBANGUNAN PEMERINTAH DAERAH KABUPATEN PEKALONGAN - Purwoko Purwoko (Program Studi Sarjana (S1) Ilmu Pemerintahan, FISIP, Universitas Diponegoro, 2015)
Developmental process has been implementasi sing in indonesia since 1969, about almost 45 years. As long as time developmental mean as physical developmental in any aspects meters as GNP, Income Percapita and Economic Growth the indicators coult not described the real developmental results in such country or such area it is needed another non eonomic variables as social variables whick some indicators as evendestribusion, evenhealth cares in one composite. Inditional social variabless ould describe development performence of Pekalongan lokal Government (Kabupaten Pekalongan) more comprehensive. Reminded that developmental performance the main pillar of state stability.